INFORMATION SYSTEM FOR PROCESSING FILE SALES EXECUTIVE IN VOTA MOTOR BANDUNG - Herwan Suwandi (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2013)
When information technology hit Indonesia in the early 90s, Executive Information System (EIS = Executive Information System) is one of the many features offered by the software maker to the company. Modules are intended for members of the Board of Directors and Senior Manager offers easy - certain facilities for the main actors of this business to conduct direct control cheaf of the company.Executive Information System that the author made is the development of database applications, namely MIS (Management Information System). Design and character of these information systems tailored to the acceleration of existing facilities adjusted acceleration of activities undertaken. The tendency of executives looking at an information must be poured neatly within the existing scope of analysis, rather than mere observation of the data that already exists. Problems that occur during this on company case studies that the authors make is how to get the management of dynamic data in the presentation of information and support executives to obtain important information and how to create an information system that can display data or reports each layer management. With built-party management application is expected to more easily obtain important information from the application of the SIE.